2014
DOI: 10.1530/eje-13-0517
|View full text |Cite
|
Sign up to set email alerts
|

Refined association of TSH receptor susceptibility locus to Graves' disease in the Chinese Han population

Abstract: Background: Convincing evidence has demonstrated the association of TSH receptor (TSHR) with Graves' disease (GD) in the Chinese Han population. Objective: The aim of this study was to identify the causal variants for GD in the region encompassing TSHR by a refining association study. Design and methods: GD patients (1536) and 1516 sex-matched controls were recruited in the first stage, and an additional 3832 GD patients and 3426 sex-matched controls were recruited in the replication stage. Genotyping was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…They focused in a 665-kb LD block harbouring the strongest TSHR association, corroborating intron 1 rs12101261 and rs179243 SNPs as independent GD susceptibility variants in the replication stage and in combined populations (5 300 GD cases and 4 916 controls) [83]. Intron 7 SNPs described by Hiratani et al [82] were not significantly associated with GD in this large Chinese cohort.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…They focused in a 665-kb LD block harbouring the strongest TSHR association, corroborating intron 1 rs12101261 and rs179243 SNPs as independent GD susceptibility variants in the replication stage and in combined populations (5 300 GD cases and 4 916 controls) [83]. Intron 7 SNPs described by Hiratani et al [82] were not significantly associated with GD in this large Chinese cohort.…”
supporting
confidence: 68%
“…It was suggested that these 3 amino acid changes could constitute GD specific mutations but their frequent presence in healthy individuals ruled them out. Despite the positive results of some association studies [73][74][75], subsequent case-control reports largely rejected an association with GD for either of these TSHR SNPs in both Caucasian [76][77][78][79][80] However, the main associated SNPs were unexpectedly located between introns 7 and 8 of the TSHR [82]. Several studies in Caucasians failed to confirm this association [87][88][89].…”
mentioning
confidence: 99%
“…Strongest SNP associations were rs179247 (OR = 1.53) and rs12101255 (OR = 1.55), which were replicated in Polish-Caucasian cohorts. A different study showed that two SNPs (rs12101261, rs179243) in intron 1 are associated with GD in Chinese population [37]. However these polymorphisms are in linkage disequilibrium with SNP's previously reported in Caucasian populations.…”
Section: Discussionmentioning
confidence: 88%
“…Dopamine-secreting PPGL are even rarer entities and can evade this strongly reassuring test. To date, their incidence is limited to case reports and only 53 have been described in the literature 1, 2, 3, 4, 5. Eisenhofer et al 2 defines dopamine secreting PPGL as tumors that produce dopamine (or its metabolite 3-methoxytyramine) greater than the combined concentrations of noradrenaline and adrenaline (or their metabolites), and corresponds to the biochemical findings in this case.…”
Section: Introductionmentioning
confidence: 92%
“…The sensitivity of plasma and urine metanephrines is close to 100% according to Van Berkel et al 1 . Metanephrine-negative PPGL is rare.…”
Section: Introductionmentioning
confidence: 97%